Exploring correlations between Conners’ Continuous Performance Test and subjective measures of attention deficit hyperactivity disorder symptoms in a paediatric clinical sample - Xue Wei Wendy Poh; Shernice Shi Yun Lim; Ying Yin Chew; Nikki Shi Jie Lim-Ashworth; Choon Guan Lim (Singapore Medical Journal)
Introduction: Attention deficit hyperactivity disorder (ADHD) is a childhood-onset neurodevelopmental condition characterised by inattention and/or hyperactivity–impulsivity. The ADHD symptoms are often evaluated and quantified using various assessment tools, such as the Conners’ Continuous Performance Test II (CCPT-II), ADHD Rating Scale (ADHD-RS), Child Behaviour Checklist (CBCL), Clinical Global Assessment Scale (CGAS) and Clinical Global Impression Scale (CGIS). This study sought to compare CCPT-II with parent- and clinician-rated rating scales (ADHD-RS, CBCL, CGAS and CGIS) in measuring the core ADHD symptoms within the paediatric ADHD population. Methods: The data, gathered from a large-scale randomised controlled trial involving 172 children aged 6–12 years with ADHD, was pooled, and a Pearson correlation analysis was conducted. Results: No significant correlations were observed between CCPT-II and ADHD-RS, as well as the various subscales of CBCL, CGAS and CGIS. Conclusion: While CCPT-II may offer insights into ADHD symptomatology, its relationship with parent- and clinician-rated rating scales such as ADHD-RS, CBCL, CGAS and CGIS appears limited. Further research is warranted to elucidate the nuances of these assessment tools and their roles in evaluating ADHD.